International exchange students KMITL-UiTM: fostering interdisciplinary excellence / Amirul Hakim Zulkifli, Hasiful Fata Talhah and Shahrool Rezza Salim - Zulkifli, Amirul Hakim; Talhah, Hasiful Fata; Salim, Shahrool Rezza (UiTM Global @ Office of International Affairs, 2024)
We are delighted to introduce one of our collaborative programs between King Mongkut’s Institute of Technology Ladkrabang (KMITL), Thailand and Universiti Teknologi MARA (UiTM) Pulau Pinang Branch that was held on May 25 to June 2023. It was designed to enhance interdisciplinary learning, research, and innovation. This innovative partnership has brought together the strengths and expertise of both universities in creating a dynamic academic environment that benefits not only students and institutions, but communities of both countries.